Novel AIEEgens: Small Structure Modification with Significant Property Change - Long, Zongze; Niu, Yadi; Zhang, Ruili; Li, Jiajia; Chu, Xianglong (Synthesis, 2025)
In this study, a series of small molecules based on 3-(dimethylamino)-1-(2-hydroxyphenyl)-2-propen-1-one have been prepared under mild reaction conditions. Most of the compounds showed high fluorescence quantum yield in the solid-state (ΦFmax = 0.75). In addition, the fluorescence emission color was effectively and simply changed by modifying the substituent on the aromatic ring. The crystalline state and the photophysical properties of all the compounds in THF(DMF)/water mixtures were investigated, exhibiting marked aggregation-induced enhanced emission characteristics. The X-ray crystallographic analysis explained the different emissions of these compounds.
Keywords: AIEE; solid-state fluorescence; color-tunable-emission; small molecules; high fluorescence quantum yield